Möjligheternas skolgård : om att skapa förutsättningar för en välanvänd utemiljö - exempel från Luleå - Johansson, Malena (SLU/Dept. of Urban and Rural Development, 2007)
Children's need of a good environment of playing outdoor at schoolyards is, both from a perspective of commonly public's health and from the children themselves, indisputable. Children who have a good and varying playground develop physically, psychologically and socially. As an instrument of pedagogic a playground also is valuable for example in teaching the round, periodical successions and understanding of democratic processes. The conception playground means here in my work the environment outdoor for children at schools up to about twelve years old.